Bat algorithm with oscillation element. (2015) - Cai, Xingjuan; Li, Wuzhao; Kang, Qi; Wang, Lei; Wu, Qidi
Bat algorithm is a novel swarm intelligent algorithm inspired by the echolocation behaviour of bats. However, the exploration capability is not well for some multi-model problems. In this paper, the control theory is applied to analyse the exploration behaviour for each bat, theoretical result shows the update manner in the standard version of bat algorithm can be viewed as a special case of oscillation element. Therefore, a new variant of bat algorithm, called bat algorithm with oscillation element, is designed. Different from the standard version, frequency is set to negative in this new variant. Furthermore, a new parameter, inertia weight is employed to provide a balance between exploitation and exploration. To test the performance, the CEC2013 shifted and rotated benchmark problems are used to compare, simulation results show our method is validity.